An improved approach of salting-out solvent-free microwave mediated rotary distillation for essential oil preparation from fresh leaves of magnolia (Oyama sieboldii) - Yang, Xinyu; Zhao, Ru; Wei, Mengxia; Gu, Huiyan; Li, Jialei; Yang, Lei; Liu, Tingting (Food Chemistry: X, 2022)
•Salting-out solvent-free microwave rotary distillation to obtain essential oil.•MgCl2 was selected as a salting-out agent from a wide range of metal salts.•During the whole process, the material is in a rotating state and is heated evenly.•Essential oil was prepared from fresh leaves of Oyama sieboldii.•The main component of O. sieboldii essential oil were dehydrocostuslactone. An improved method denoted as salting out-solvent-free microwave rotary distillation (SOSFMRD) was successfully developed for the extraction of essential oils from fresh magnolia (Oyama sieboldii) leaves, in which we achieved the rotation of the reaction material by means of a rotating motor to subject the material to uniform microwave irradiation. Magnesium chloride was selected as the salting-out agent through a comparative study on the salting-out effects of different anions and cations of metal salts. The variables of SOSFMRD were systematically optimized. Under the obtained optimization conditions, the essential oil yield was 21.68 ± 1.02 mL/kgDW. Gas chromatography–mass spectrometry analysis showed that the main chemical constituent of O. sieboldii essential oil was dehydrocostuslactone, the content of which reached 30.23 ± 1.27 %. Compared with the other conventional methods, this method has a high yield and low energy consumption, which can effectively reduce impact on the environment.